THE MOUSEDEER: THE SIMBOL OF LOWER CLASS’ RESISTANCE AGAINTS THE RULING GROUP - LABANIA - - (MOZAIK HUMANIORA, 2019)
This studi aims to reveal the constructed values in the story of the mousedeer through a social class approach. This study analyzes three types of the mousedeer stories considered to contain any social symbols that could lead to the representation of certain social groups. This study is based on Stuart Hall’s theory of Representation and Karl Marx’s theory of Social Class. The result of the analysis shows that the mousedeer stories contain the representation of class structures as there occured in people’s social relations. The stories contain conflict between social classes or class struggle caused by inequality in the ownership of power, where there are the opposing parties acting as the owner of this power and the mousedeer as the representation of parties without power. Here, the mousedeer who always be able to get away by tricking his strong opponents is a symbol of resistance against them, the onces who owns the power, the authority. These mousedeer stories also has a potential to indicate the psychological turmoil or expression of the lower society who tries to oppose the ruling repression in their era.